The Relationship Between Stress and Vaginal Discharge in Adolescent Girls at Bali Medika Denpasar Health Vocational School in 2022 - Ayu Trisna Suciari; Ni Nyoman Budiani; Ni Wayan Armini (Jurnal Ilmiah Kebidanan (The Journal Of Midwifery), 2023)
Vaginal discharge is one of the problems that has long been a problem for you women, including young women. One of the factors that cause vaginal discharge in adolescent girls is stress, both physical and psychological stress. The purpose of this study was to determine whether there is a relationship between stress and the incidence of vaginal discharge in adolescent girls at SMK Kesehatan Bali Medika Denpasar in 2022. The research method used was analytical correlation with a cross sectional approach. The sampling technique was proportionate stratified random sampling, with a sample size of 51 people. Data collection techniques using a questionnaire. The results of the univariate analysis showed that as many as 17 (33%) young women did not experience stress and as many as 34 people (67%) experienced stress. Most of the young women experienced physiological vaginal discharge as many as 40 people (78%) and pathological vaginal discharge as many as 11 people (22%). The results of the bivariate analysis with the Lambda Contingency Coefficient stated that there was a relationship between stress and the incidence of vaginal discharge with a p value = 0.002 and a correlation value (rho) = 0.6. There is a significant relationship with a moderate level of strength between stress and the incidence of vaginal discharge in young women at the Health Vocational School of Bali Medika Denpasar in 2022. Researchers suggest to further researchers to develop research with different variables related to other factors that cause the incidence of vaginal discharge in adolescent girls.